Barriers and facilitators to the utilization of the intensive adherence counselling framework by healthcare providers in Uganda: a qualitative study - Musinguzi, Pius; Najjuma, Josephine Nambi; Arishaba, Adellah; Ochen, Eric; Ainembabazi, Racheal; Keizirege, Fred; Sabano, Racheal Lillian; Wakida, Edith K.; Obua, Celestino (BMC Health Services Research, 2022)
Background: Uganda Ministry of Health (UMOH) embraced the World Health Organization recommendation for people living with human immune deficiency virus with a detectable viral load (VL) exceeding 1000 copies/mL to receive intensive adherence counselling (IAC). The IAC framework was developed as a step-by-step guide for healthcare providers to systematically support persons with non-suppressed VL to develop a comprehensive plan for adhering to treatment. The objective of this study was to explore the current practice of the healthcare providers when providing IAC, and identify the barriers and facilitators to the utilization of the UMOH IAC framework at two health centers IV level in rural Uganda. Methods: This was a descriptive cross-sectional qualitative study that explored the current practices of the health care providers when providing IAC, and identified the barriers and facilitators to the utilization of the UMOH IAC framework. We used an interview guide with unstructured questions about what the participants did to support the clients with non-suppressed VL, and semi-structured questions following a checklist of categories of barriers and facilitators that affect ‘providers of care’ as provided by the Supporting the Use of Research Evidence for policy in African health systems (SURE) framework. Current practice as well as the categories of barriers and facilitators formed the a priori themes which guided data collection and analysis. In this study we only included healthcare providers (i.e., medical doctors, clinical officer, nurses, and counsellors) as ‘providers of care’ excluding family members because we were interested in the health system. Results: A total of 19 healthcare providers took part in the interviews. The healthcare providers reported lack of sufficient knowledge on the UMOH IAC framework; most of them did not receive prior training or sensitization when it was first introduced. They indicated that they lacked counselling and communication skills to effectively utilize the IAC framework, and they were not motivated to utilize it because of the high workload at the clinics compounded by the limited workforce. Conclusions: Although the UMOH IAC framework is a good step-by-step guide for the healthcare providers, there is need to understand their context and assess readiness to embrace the new behavior before expecting spontaneous uptake and utilization
Keywords: Intensive adherence counselling; Barriers and facilitators; Uptake and utilization; Health care providers; SURE framework